Pembelajaran Prasekolah Berbasis Alkitab - Hasudungan Simatupang (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aims to examine the biblical foundation in the learning of Bible-based preschool children with a contextual learning approach. The research method used is topical research, which focuses on developing education and learning that is relevant to daily life so that children more easily absorb material according to learning goals. The learning process starts from simple things to more complex things, according to the stage of early childhood development. The results of the study show that Bible-based preschool learning includes various activities, including: educating children with a biblical foundation, introducing the Bible through number ordering, arranging the biblical alphabet, combining letters into words, arranging words into biblical phrases, reading Bible texts, memorizing short golden verses, and learning activities such as coloring and listening to Bible stories. These findings confirm that Bible-based learning with a contextual approach can be an effective strategy in shaping the spiritual, cognitive, and character foundations of preschoolers, while instilling faith values from an early age.